HUBUNGAN ANTARA MODEL PEMBELAJARAN KOOPERATIF MELALUI METODE EKSPERIMEN DENGAN MOTIVASI DAN HASIL BELAJAR PADA MATERI PEMBIAKAN TANAMAN SECARA GENERATIF SISWA KELAS X AGRIBISNIS SMK NEGERI 7 JAYAPURA - Gani, Robby Abdul (Jurnal Ilmu Pendidikan Indonesia, 2016)
The aim of this study were to determine: (1) to determine the relationship between cooperative learning model through experimental methods in plant breeding materials in generative learning motivation, (2) to determine the relationship between cooperative learning model through experimental methods in plant breeding materials in generative learning outcomes students, (3) to determine the improvement of student learning outcomes given the account after learning activities using learning model through experimental methods. while the experimental test dailaksanakan at SMK 7 Jayapura class X Aribisnis. While the correlation of tes results (a) cooperative learning model through experimental methods to study !motivation obtained results sig count (0,011) < 0.05 and a correlation coefficient of 0.634 means that there is a link at the level of 95 % , and the relationship to the level of a strong correlation (b) cooperative learning model through experimental method with the results of student learning sig arithmetic average RPP (0,027) < sig 0.05 and a correlation coefficient of 0.570 means that there is a link at the level of 95 % and relationships at the level of moderate correlation (c) an increase in learning outcomes between in each lesson plan because the students have started to understand and enjoy learning by using the cooperative model through experimental methods. Improved learning outcomes can also be seen from the number of students who reach the KKM reached 86.67 % . Key Word: Eksperiment Method, Learning Motivasi, Learning Results, Plant breeding materials in generative.